DRAINAGE MANAGEMENT ISSUES IN UZBEKISTAN - T. Atakulov (American Journals, 2023)
The article deals with the issues of the impact of melioration on agricultural lands. The melioration conditions of the lands of the regions of Uzbekistan are analyzed. Practical recommendations for increasing farmland with the help of optimal management are given.
Keywords: Basin Irrigation Systems Authority, State Water Special Contract Unitary Enterprises, Hydro-Geological Ameliorative Expedition, Republican Irrigated Land Amelioration Fund, Office of Governor, Ministry of Agriculture and Water Resources, Ministry of Finance, Water Consumers Association